Trastornos del sueño en los pacientes críticos - Tobar A., Eduardo; Parada M., Raúl (Revista Hospital Clínico Universidad de Chile, 2012)
Sleep disorders are common in critically ill patients, and its consequences still insufficiently clarified. An environment with multiple noxious stimuli, light and hearing, admission for severe acute illness with multisystem disease, and the need for drugs that can disrupt sleep physiology, lead to this situation. We will review the epidemiology and risk factors for these disorders, and its possible consequences. Finally we discuss potential strategies for prevention of sleep disorders in this patient population.